Phenolic Composition and Hepatoprotective Activities of Allium Hookeri Against Hydrogen‐Peroxide‐Induced Oxidative Stress in Cultured Hepatocytes. Issue 3 (9th November 2015) - Park, Soo Yeon; Je, Jae‐Young; Ahn, Chang‐Bum
Abstract: A llium hookeri were extracted with water and 80% ethanol, and their phenolic compositions, as well as their antioxidant and hepatoprotective effects against H2 O2 ‐induced damage in cultured hepatocytes were determined. High‐performance liquid chromatography analysis revealed that the water and ethanol extract were rich in phenolic compounds. The A . hookeri extracts exhibited similar scavenging activities against 2, 2‐diphenyl‐1‐picrylhydrazyl and 2, 2‐azino‐bis(3‐ethylbenzthiazoline)‐6‐sulfonic acid cation radicals. The ethanol extract exhibited a significantly ( P < 0.05) higher oxygen radical absorbance capacity value and reducing power than those of the water extract. The A . hookeri extracts protected against H2 O2 ‐induced hepatocyte damage in cultured hepatocytes through the inhibition of intracellular reactive oxygen species generation, lipid peroxidation and upregulation of intracellular glutathione levels. Notably, the hepatoprotective effects of the A . hookeri extracts were directly correlated with the increased expression of superoxide dismutase, catalase and glutathione peroxidase in cultured hepatocytes. Practical Applications: This study would informatively benefit preparation with antioxidant and hepatoprotective extracts from A llium hookeri . Ethanolic extract showed better hepatoprotective effect, which is attributed to its phenolic composition. The result provided an instruction for the preparation of A . hookeri ‐related products.